2013
DOI: 10.1016/j.toxicon.2013.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of formyl peptide receptors in the stimulatory effect of crotoxin on macrophages co-cultivated with tumour cells

Abstract: Crotoxin (CTX) is the main neurotoxic component of Crotalus durissus terrificus snake venom. It inhibits tumour growth and modulates the function of macrophages, which are essential cells in the tumour microenvironment. The present study investigated the effect of CTX on the secretory activity of monocultured macrophages and macrophages co-cultivated with LLC-WRC 256 cells. The effect of the macrophage secretory activities on tumour cell proliferation was also evaluated. Macrophages pre-treated with CTX (0.3 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 62 publications
6
32
0
11
Order By: Relevance
“…Three peaks (p1, p2 and p3) were obtained of which p2 corresponded to the pure CTX fraction (about 60% of the crude venom), and peaks 1 and 3 included the other CdtV toxins. Prior to pooling, the fractions containing CTX were tested for homogeneity by non-reducing SDS-PAGE (12.5%) (50) and the phospholipase A2 activity was assessed by a colorimetric assay using a synthetic chromogenic substrate, as previously described by our group (13,19,44,51).…”
Section: Crotoxinmentioning
confidence: 99%
See 2 more Smart Citations
“…Three peaks (p1, p2 and p3) were obtained of which p2 corresponded to the pure CTX fraction (about 60% of the crude venom), and peaks 1 and 3 included the other CdtV toxins. Prior to pooling, the fractions containing CTX were tested for homogeneity by non-reducing SDS-PAGE (12.5%) (50) and the phospholipase A2 activity was assessed by a colorimetric assay using a synthetic chromogenic substrate, as previously described by our group (13,19,44,51).…”
Section: Crotoxinmentioning
confidence: 99%
“…Both in vivo and in vitro studies have shown the dual effects of CTX on macrophage functions, such as inhibition of macrophage spreading and phagocytosis, and stimulation of H2O2 and NO production and release (13,19). These changes are accompanied by increased activity of the key glycolytic enzymes and higher consumption of glucose and glutamine, which demonstrates the metabolic effects of this toxin (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre essas, a lipoxina inibe a quimiotaxia, a adesão e a transmigração dos neutrófilos, bem como a expressão do receptor CR3 nessas células (Maderna & Godson, 2009;Ryan & Godson, 2010). Corrobora para essa hipótese, o fato de a CTX induzir a liberação de lipoxina por macrófagos em cultura (Costa et al, 2013) e por neutrófilos no tecido subcutâneo após administração de carragenina (Nunes et al, 2015, em publicação). Adicionalmente, recentemente foi demonstrado que a CTX induz a secreção de lipoxina no tecido do cólon, após a indução da inflamação intestinal (Almeida et al, 2015).…”
Section: Discussão __________________________________________________unclassified
“…Ainda, neste mesmo estudo foi observado aumento da produção de mediadores lipídicos Lipoxina A 4 e análogo mais estável 15-epi-LXA 4, que resultou no decréscimo da proliferação das células tumorais (COSTA et al, 2013).…”
Section: Estudos Experimentais Sobre Os Efeitos Antitumoral E Imunorrunclassified